Articulate storyline-based multimedia development to improve the mathematical representation skills of grade V elementary school students - Kinanti Adlina; Tri Suryaningsih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This research is motivated by the limited use of interactive multimedia, specifically designed to improve elementary school students' mathematical representation skills in integer operations materials. Previous studies have generally focused on improving learning outcomes without emphasizing mathematical representation as a key competency. Therefore, this study aims to develop and test the effectiveness of Articulate Storyline-based multimedia specifically designed to support students' mathematical representation abilities. This research uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study subjects were elementary school grade V students (n = 34) with an evaluation design using a one-group pretest–posttest. The primary instrument was a mathematical representation test, constructed based on NCTM indicators and operationalized as items assessing students' abilities to translate, interpret, and construct representations. The product's feasibility was validated by content experts (80%), subject matter experts (80%), media experts (97%), and field practitioners (96%), indicating that multimedia was in the very feasible category. The students' response to the product's practicality was also very good, with an average score of 96.42%. The results of the effectiveness test showed a significant improvement in students' mathematical representation abilities after using multimedia (p < 0.001), indicating that the product is not only feasible and practical but also pedagogically effective. The novelty of this research lies in the development of interactive multimedia in Articulate Storyline that explicitly integrates mathematical representation indicators into content design and learning activities. These findings make a practical contribution to the development of technology-based mathematics learning media aimed at strengthening the mathematical representation competence of elementary school students.